Distribution and Abundance of Non-Breeding Shorebirds Along the Coasts of the Buenos Aires Province, Argentina - Blanco, Daniel Ezequiel Roberto; Yorio, Pablo Martin; Petracci, Pablo; Pugnali, Germán
The coast of the Buenos Aires province, Argentina, includes a remarkable diversity of habitats and is used by more than fifteen nearctic shorebird species during the austral summer months. We evaluated non-breeding shorebird distribution and abundance patterns along the Buenos Aires coastal zone and determined shorebird use of different coastal landscapes. Surveys were conducted in December 2000, and January and February 2001, using line-transect methods. The data were classified based on five previously defined coastal landscapes. Fifty four localities were surveyed covering 93 kilometers of coastline. A total of 44 waterbird species corresponding to 13 families were recorded. Shorebirds (Scolopacidae, Charadriidae, Haematopodidae and Recurvirostridae) accounted for approximately 45% of recorded waterbirds, including 14 nearctic species. Shorebird species recorded per locality varied from one to eleven, with 61% of the localities having one to four species. The most common were the American Oystercatcher (Haematopus palliatus), White-rumped Sandpiper (Calidris fuscicollis), Two-banded Plover (Charadrius falklandicus), American Golden-Plover (Pluvialis dominica) and the Sanderling (Calidris alba). Shorebird species richness and abundance varied significantly among coastal landscapes, with the highest values recorded in estuarine saltmarshes of Bahía Samborombón and Bahía Blanca. Among marine landscapes, the highest abundance and number of species were recorded in sandy beaches with “restinga” patches. This study confirms that shorebirds are an important component of the birdlife in the Buenos Aires coastal zone during the austral summer months, and that their distribution is not homogeneous along the coast, with species richness and abundances varying among localities depending on coastal landscapes. Fil: Blanco, Daniel Ezequiel Roberto. Wetlands International; Argentina Fil: Yorio, Pablo Martin. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro ...